2021
DOI: 10.3390/atmos12081067
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Air Pollution Tolerance and Particulate Matter Accumulation of 11 Woody Plant Species

Abstract: High concentration of particulate matter (PM) threatens public health and the environment. Increasing traffic in the city is one of the main factors for increased PM in the air. Urban green spaces play an important role in reducing PM. In this study, the leaf surface and in-wax PM (sPM and wPM) accumulation were compared for 11 plant species widely used for landscaping in South Korea. In addition, biochemical characteristics of leaves (ascorbic acid chlorophyll content, leaf pH, and relative water content) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…I. sanguinea showed a significant difference in wax content (Table 3) by PM sources, but the mean was 2-3 times higher in treatment, implying that wax content and wPM10 of I. sanguinea may have affected each other. In general, sPM is higher than wPM in many studies (Przybysz et al, 2014: Popek et al, 2017: Bui et al, 2021. However, in a study by Przybysz et al (2014), wPM was higher than sPM in Pinus sylvestris in February when there is much rainfall, and there was more wax content than other seasons as well.…”
Section: Experiments Methods and Data Analysismentioning
confidence: 83%
See 1 more Smart Citation
“…I. sanguinea showed a significant difference in wax content (Table 3) by PM sources, but the mean was 2-3 times higher in treatment, implying that wax content and wPM10 of I. sanguinea may have affected each other. In general, sPM is higher than wPM in many studies (Przybysz et al, 2014: Popek et al, 2017: Bui et al, 2021. However, in a study by Przybysz et al (2014), wPM was higher than sPM in Pinus sylvestris in February when there is much rainfall, and there was more wax content than other seasons as well.…”
Section: Experiments Methods and Data Analysismentioning
confidence: 83%
“…Zhang et al (2020) reported that PM capturing capacity of plants, air pollution tolerance index (APTI), and antioxidant systems can be used as indicators to select suitable plant species in green belt construction. Bui et al (2021) compared the accumulative amount of PM and APTI with 11 species of woody plants and reported that Pinus strobus showed the highest PM accumulation and APTI, whereas Cercis chinensis showed the lowest.…”
Section: Introductionmentioning
confidence: 99%
“…Positive changes take place in the aesthetics of the areas [ 122 ], while the sense of safety and health of the local residents grows. Simultaneously, plants reduce air pollution [ 123 ]. In addition, the benefits of gardening have a positive effect on people’s physical and mental health.…”
Section: Is Regenerative Agriculture Really the Solution To The Probl...mentioning
confidence: 99%
“…Moreover, Arkadiusz et al [37] found that PM has a negative correlation with the chlorophyll content but that association is unique to each plant species. However, with the same environment condition, the level of decrease in chlorophyll is depended on the plant species [38] .…”
Section: Heavy Metalsmentioning
confidence: 99%